Proportion of neuropathic pain in the back region in chronic low back pain patients -a multicenter investigation. Issue 1 (December 2018) - Li, Jun; He, Jing; Li, Hu; Fan, Bi-Fa; Liu, Bo-Tao; Mao, Peng; Jin, Yi; Cheng, Zhu-Qiang; Zhang, Ting-Jie; Zhong, Zhi-Fang; Li, Si-Ji; Zhu, Sai-Nan; et al.
Abstract Neuropathy can contribute to low back pain (LBP) in the region of the back. Our study investigated the proportion of neuropathic pain (NP) in low back region in chronic LBP patients from multicenter and clinics in China and identified associated factors. Assessment was made using a questionnaire and the Leeds Assessment of Neuropathic Symptoms and Signs (LANSS, only tested in low back region), as well as Quantitative Sensory Testing (QST, merely applied to the low back region), the Hospital Anxiety and Depression Scale (HADS) and the Oswestry Disability Index (ODI). Our questionnaire collected demographic information, behavioral habits and medical records. 2116 outpatients over 18 years old complaining of LBP lasting more than 3 months were enrolled in this study. The NP proportion in low back region in chronic LBP patients was 2.8%. Multivariable logistic regression analysis showed that histories of lumbar surgery, abdominal or pelvic surgery, and drinking alcohol were independent positive predictors for LBP of predominantly neuropathic origin (LBNPO), while history of low back sprain and frequently carrying weight as independent negative predictor. Using these parameters may help the identification of patients with chronic LBP likely to develop NP leading to improved treatment outcomes.